2022
DOI: 10.1371/journal.pone.0278226
|View full text |Cite
|
Sign up to set email alerts
|

Effect of physical activity on the risk of frailty: A systematic review and meta-analysis

Abstract: Objective The relationship between physical activity (PA) and the risk of frailty has not reached a conclusive result. This systematic review with meta-analysis aimed to evaluate the effect of PA on the onset of frailty in the community-dwelling middle and older age adults by pooling data from cohort studies. Methods A systematic literature search was performed via PubMed, Embase, and Web of Science up to June 01, 2021. Pooled adjusted effect estimates (ES) with 95% confidence interval (CI) were calculated b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 58 publications
0
20
0
2
Order By: Relevance
“…[50] Another recent review [51] revealed that e-health and m-health technologies increase physical activities, which could improve the frailty status. [52] Therefore, internet access among middle-aged and older adults would be helpful to build a healthy aging society.…”
Section: Discussionmentioning
confidence: 99%
“…[50] Another recent review [51] revealed that e-health and m-health technologies increase physical activities, which could improve the frailty status. [52] Therefore, internet access among middle-aged and older adults would be helpful to build a healthy aging society.…”
Section: Discussionmentioning
confidence: 99%
“…26 Regarding physical factors, an increasing physical activity level may promote appetite or gastric emptying in older adults, thus increasing their food intake 27 as well as reducing the risk of frailty. 28 Moreover, an intervention study has shown that a 12-week stepping-based aerobic exercise program effectively improved fatigue and frailty in older adults with multimorbidity. 29 In addition, physical activity has been shown to prevent the deterioration of physical functions such as gait speed, grip strength, and even sarcopenia.…”
Section: Discussionmentioning
confidence: 99%
“…However, poor oral status has been reported to strongly predict new‐onset frailty and mortality in community‐dwelling older adults 26 . Regarding physical factors, an increasing physical activity level may promote appetite or gastric emptying in older adults, thus increasing their food intake 27 as well as reducing the risk of frailty 28 . Moreover, an intervention study has shown that a 12‐week stepping‐based aerobic exercise program effectively improved fatigue and frailty in older adults with multimorbidity 29 .…”
Section: Discussionmentioning
confidence: 99%
“…Inhaltlich sollen nach dieser Leitidee die körperliche Fitness und das Aktivitätsverhalten der Personen regelmäßig bewertet und mittels personalisierter Interventionsmethoden in der Therapie und Nachsorge gefördert werden. Auch in Bezug auf die Entwicklung der Frailty erweist sich regelmäßige körperliche Aktivität als präventiv (s. Beitrag "Frailty: Prävention", S. 155) [4]. Hierbei beschreibt körperliche Aktivität jede von der Skelettmuskulatur ausgeübte Bewegung, die den Energieverbrauch über den Grundumsatz erhöht.…”
Section: Exercise Is Medicineunclassified